PENGARUH BURN OUT DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI PT BANK MEGA SYARIâAH CABANG MALANG - Maharani, Vivin (IQTISHODUNA, 2013)
This research investigates the extent to which Burnout and Emotional Intelligence impacts on theÂ  work performance of employee. This research sets its goal to knowÂ  the significant influence of Burnout and Emotional Intelligence toward the performance of employee Bank Mega Syariâah Malang.This is explanatory research which has goal o test defined hypothesis on the influence of burnout and Emotional Intelligence toward the work performance of employee. The research populationÂ  involved 32 employee of Bank Mega Syariâah Malang.Â  Quistionnaire is used as research instruments in this research. This research employs path analysis to statistically analyze the data in which the coefficient determinants is set on 0,05 level. The result of the research analysis proves thatÂ  Burnout and Emotional Intelligence simultaneously give significant influence on the work performance employee with determination coefficientÂ  shows 0,468. Based on finding, it is further suggested that leader on Bank Mega syarâah Malang should give more attention to theÂ  Burnout and Emotional Intelligence. The result of this research proves that Burnout and Emotional Intelligence simustaneously give significant influence on work performance.